(untitled) (Baghdad Science Journal, 2022)
Urinary tract infections (UTIs) mean microbial pathogens in the urethra or bladder (lower urinary tract). Important risk factors for recurrent UTI include obstruction of the urinary tract, use of a bladder catheter or a suppressed immune system. This study aims to isolate and identify bacteria from patients with TCC-bladder cancer or patients with a negative cystoscope and estimate antibiotic susceptibility patterns and evaluate some of the virulence factors. From a total of 62 patients with TCC-BC or negative cystoscope, only 35 favorable bacterial growths were obtained, including Escherichia coli (UPEC), a significant bacterial isolate, and Stenotrophomonas maltophilia. The percentage of multi drug-resistance bacteria (MDR) was identified in (62.8%) while the extended drug-resistance bacteria (XDR) was (28.5%). All isolates were producer for biofilm either moderately 18/35 (49%) or strongly 18/35 (51%). Only 25/35 (71%) isolates were produced for siderophore, while 10/35 (29%) isolates were non-produced. Inducing cytochrome P450 expression protein was seen in (14/35) 40% isolates. In conclusion, patients with TCC-BC or negative cystoscope who had a urinary catheter or immune-compromised were at high risk of infecting with nosocomial or opportunistic pathogens, which could be develop antibiotic resistance, the central problem in the cohort of patients undergoing chemotherapy or immune cancer therapy